2022
DOI: 10.1161/hypertensionaha.122.20022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relationship Between Arterial Stiffness and Systolic Blood Pressure Under Intensive or Standard Control: A Post Hoc Analysis of the STEP Trial

Abstract: Background: Whether or not the temporal relationship between arterial stiffness and systolic blood pressure (SBP) is affected by how strictly SBP is controlled (intensive, 110–<130 mm Hg; standard, 130–<150 mm Hg) has been unclear. Methods: The temporal relationship between brachial-ankle pulse wave velocity (baPWV) and SBP was assessed using a cross-lagged panel model in the 5369 participants in the STEP trial (Strategy of Blood Pressure Interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…High BP was another risk factor linked to a faster increase in baPWV [6] in the STEP trial (Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients) of a cross-lagged panel model in the 5369 participants. In both the intensive treatment groups (SBP target, 110-130 mm Hg) and standard treatment groups (SBP target, 130-150 mm Hg), arterial stiffness measured by baPWV was a consistent predictor of SBP and made it more difficult to achieve target SBP, especially in the intensive therapy group [23]. Chronic renal failure is also a risk factor for arterial stiffness [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…High BP was another risk factor linked to a faster increase in baPWV [6] in the STEP trial (Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients) of a cross-lagged panel model in the 5369 participants. In both the intensive treatment groups (SBP target, 110-130 mm Hg) and standard treatment groups (SBP target, 130-150 mm Hg), arterial stiffness measured by baPWV was a consistent predictor of SBP and made it more difficult to achieve target SBP, especially in the intensive therapy group [23]. Chronic renal failure is also a risk factor for arterial stiffness [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when a pharmacological agent reduces mean blood pressure, it lowers arterial stiffness as well [ 32 ]. In this regard, a recent post hoc analysis of the STEP trial (Strategy of Blood Pressure Intervention in the Elderly Hypertensive Patients) confirmed that arterial stiffening precedes SBP in both the intensive and standard treatment groups, and it led to difficulty in reaching target SBP, particularly in the intensive treatment group [ 153 ]. In the same study, assignment to the intensive treatment group was associated with an attenuation of the age-related increase in arterial stiffness assessed with the baPWV at 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…At least, no clear relationships of those changes with urate-lowering were found in this study (Additional file 6 : Table S5), and the beneficial vascular effects might have been partly caused by selective and direct URAT1 inhibition by dotinurad at the urate-entry site on vascular walls and resultant attenuation of ROS production [ 8 , 9 ]. In particular, arterial stiffening is a key driver of hypertension and could be a therapeutic target in its care [ 38 , 39 ]. Considering the pathophysiological roles of those markers in the development and progression of cardiometabolic diseases, dotinurad may have the potential to cause off-target effects, which favorably influence vascular properties and cardiovascular and metabolic health status.…”
Section: Discussionmentioning
confidence: 99%